Telemedicine Provides Noninferior Research Informed Consent for Remote Study Enrollment: A Randomized Controlled Trial. (18th June 2016) - Bobb, Morgan R.; Van Heukelom, Paul G.; Faine, Brett A.; Ahmed, Azeemuddin; Messerly, Jeffrey T.; Bell, Gregory; Harland, Karisa K.; Simon, Christian; Mohr, Nicholas M.
Abstract: Objective: Telemedicine networks are beginning to provide an avenue for conducting emergency medicine research, but using telemedicine to recruit participants for clinical trials has not been validated. The goal of this consent study was to determine whether patient comprehension of telemedicine‐enabled research informed consent is noninferior to standard face‐to‐face (F2F) research informed consent. Methods: A prospective, open‐label randomized controlled trial was performed in a 60, 000‐visit Midwestern academic emergency department (ED) to test whether telemedicine‐enabled research informed consent provided noninferior comprehension compared with standard consent. This study was conducted as part of a parent clinical trial evaluating the effectiveness of 0.12% oral chlorhexidine gluconate in preventing hospital‐acquired pneumonia among adult ED patients with expected hospital admission. Prior to being recruited into the study, potential participants were randomized in a 1:1 allocation ratio to consent by telemedicine versus standard F2F consent. Telemedicine connectivity was provided using a commercially available interface (REACH platform, Vidyo Inc.) to an emergency physician located in another part of the ED. Comprehension of research consent (primary outcome) was measured using the modified quality of informed consent (QuIC) instrument, a validated tool for measuring research informed consent comprehension. Parent trial accrual rate and qualitative survey data were secondary outcomes. Results: A total of 131 patients were randomized ( n = 64, telemedicine), and 101 QuIC surveys were completed. Comprehension of research informed consent using telemedicine was not inferior to F2F consent (QuIC scores 74.4 ± 8.1 vs. 74.4 ± 6.9 on a 100‐point scale, p = 0.999). Subjective understanding of consent (p = 0.194) and parent trial study accrual rates (56% vs. 69%, p = 0.142) were similar. Conclusion: Telemedicine is noninferior to F2F consent for delivering research informed consent, with no detected differences in comprehension and patient‐reported understanding. This consent study will inform design of future telemedicine‐enabled clinical trials.